Impact of nasal photodisinfection on SARS-CoV-2 infection in an industrial workplace - Richard Rusk; Judy Hodge (Elsevier, 2023)
Objectives: We aimed to evaluate a quality improvement initiative designed to control SARS-CoV-2 (COVID) using the large-scale deployment of antimicrobial photodisinfection therapy (aPDT) for nasal decolonization in a Canadian industrial workplace (a food processing plant). Study design: Using a retrospective chart review of treatment questionnaires, linked to COVID laboratory testing results, a quality improvement assessment was analyzed to determine treatment effectiveness and safety. Methods: This voluntary aPDT intervention involved the administration of a light-sensitive liquid to the nose followed by nonthermal red-light irradiation on a weekly basis. Employees in food processing industries are at increased risk for COVID infection due to the nature of their work environments. In an effort to mitigate the transmission and consequences of the disease among such workers and the community at large, aPDT was added to a well-established bundle of pre-existing pandemic safety measures (e.g., mask-wearing, testing, contact tracing, workplace-engineered barriers, increased paid sick leave). Results: From December 2020 to May 2021, we found high interest in and compliance with aPDT treatment, along with a statistically significant lower PCR test positivity rate in the study population in comparison to the case rates for the local Canadian province. Treatment safety monitoring and outcomes of the aPDT program demonstrated no serious adverse events. Conclusions: This study suggests nasal photodisinfection provides safe and effective COVID viral suppression when deployed across the majority of workers in an industrial workplace setting.